High-Frequency Ultrasonography and Evaporimetry in Non-invasive Evaluation of the Nail Unit - Szymoniak-Lipska, Marta; Polańska, Adriana; Jenerowicz, Dorota; Lipski, Adam; Żaba, Ryszard; Adamski, Zygmunt; Dańczak-Pazdrowska, Aleksandra (Frontiers in Medicine, 2021)
Introduction Evaporimetry and HF-USG due to their availability of equipment and low research costs seem to be particularly noteworthy, but so far have been assessed to a limited extent. The aim of presented study was to check the usefulness of TOWL and HF-USG in examination of NU. Material and methods 58 volunteers aged 25-65 years (mean age: 41 ± 10.16 years) were qualified to the study. The subjects did not present symptoms of clinically evident onychopathy and did not suffer from any dermatoses associated with lesions occuring within the NU. In all volunteers the measurement of TOWL and 20 MHz ultrasoography (High frequency ultrasonography, HF-USG) with the special emphasis on determination of nail plate thickness were performed. Results Analyzis of 464 HF-USG images revealed that the nail plate presented as two hyperechoic, parallel streaks (railway sign) with a linear hypoechoic middle layer between them. Matrix was visualized as a hypoechoic structure with blurred boundaries, mostly within the fourth and fifth fingers and more often in women. We found statistically significant correlations between the type of a finger and the thickness of the nail plate both in the entire study group and taking into account gender. There were statistically significant differences in the thickness of the nail plates of the corresponding types of fingers between female and male NUs. Statistically significant correlations were found between the type of a finger and the TOWL value in the whole group and taking into account gender (p<0.05), except of non-dominant hand in men. There were no statistically significant differences in the TOWL values of the corresponding types of fingers between male and female NUs (p>0.05). There was no statistically significant correlation between the TOWL value and the nail plate thickness. Conslusions Non-invasive methods, such as HF-USG and TOWL enable assessment of the NU and are useful in examination of its structure and function. HF-USG shows characteristic elements of NUs, that can be distinguished because of differences in their echogenicity. The thickness of the nail plate and TOWL depend on the type of finger, and show a relationship with gender.